Pathological Alteration in the Choroid Plexus of Alzheimer’s Disease: Implication for New Therapy Approaches - Krzyzanowska, Agnieszka; Carro, Eva (Frontiers in Pharmacology, 2012)
Morphological alterations of choroid plexus in Alzheimer´s disease (AD) have been extensively investigated. These changes include epithelial atrophy, thickening of the basement membrane and stroma fibrosis. As a result, synthesis, secretory, and transportation functions are significantly altered resulting in decreased cerebrospinal fluid (CSF) turnover. Recent studies discuss the potential impacts of these changes, including the possibility of reduced resistance to stress insults and slow clearance of toxic compounds from CSF with specific reference to the amyloid peptide. Here, we review new evidences for AD-related changes in the choroid plexus. The data suggest that the significantly altered functions of the choroid plexus contribute to the multiparametric pathogenesis of late-onset AD.